Chapter 8: Trillium Health Centre - Mississauga, Ontario (Books, 2008)
Citation Information Baker, G.R., A. MacIntosh-Murray, C. Porcellato, L. Dionne, K. Stelmacovich and K. Born. 2008. "Trillium Health Centre." High Performing Healthcare Systems: Delivering Quality by Design. 245-266. Toronto: Longwoods Publishing. • View the individual chapters for free in the Table of Contents. To order the print version please call Barbara Marshall at 416-864-9667